Zenonian Laws on Sea Views and the Image of the City of Lisbon - Carita,Hélder (2019)
Following the 1755 earthquake, the royal decree that issued directives for the rebuilding of the city of Lisbon emphatically declared the abandonment of the Constitution of Zeno. This decree had its origins in Roman Law and the Code of Justinian, protecting the views from houses facing the sea and, in the case of Lisbon, views over the River Tagus. Although historiographers of urbanism consider this law to be either extinct or forgotten, it was upheld for centuries in Portugal and had a significant bearing on the city's architecture, helping to mold an urban culture that prized Lisbon's visual features and landscapes. I propose to examine the way in which these laws were incorporated into, and applied within, Portuguese law. Above all, I examine how they were understood and experienced in the day-to-day life of the city, where, in the various records of petitions, agreements, contracts, and legal disputes, we can find constant references to these laws, which became a source of privilege and a zealously guarded asset, particularly among the social elite.